Managerial incentives and favoritism in promotion decisions: Theory and field evidence - Johannes Berger; Claus Herbertz; Dirk Sliwka (Institute for the Study of Labor (IZA), 2011)
This paper investigates the effects of managerial incentives on favoritism in promotion decisions. First, we theoretically show that favoritism leads to a lower quality of promotion decisions and in turn lower efforts. But the effect can be mitigated by pay-for-performance incentives for managers who decide upon promotion. Second, we analyze matched employer-employee survey data with detailed firm level information on managerial incentive schemes and find that perceived promotion quality is indeed substantially higher when managers receive performance-related pay or participate in gain sharing plans.
urn:nbn:de:101:1-201104133606
Keywords: J33; M51; M52; M54; J71; 330; incentives; favoritism; nepotism; tournaments; Erwerbsverlauf; Personalauswahl; Führungskräfte; Patronage; Leistungsentgelt; Extensives Spiel; Theorie; Feldforschung